(In)Desejáveis? trabalho imigrante e precarização em tempos de crise - Manjabosco, Adriele Marlene (2020)
This dissertation has as object of study the work of international migrants. The objective is to analyze the determinants of precarious migrant work in Rio Grande do Sul, in the context of capital crisis. The process of investigation and exposition was guided by the dialectical-critical method contemplating the categories historicity, totality, contradiction and mediation. With the transformation of reality as its purpose, it aims to contribute with subsidies for the expansion of public policies aimed at these segments. The research was conducted under the quanti-quali approach, with emphasis on the qualitative aspect and is constituted with empirical and documentary analysis. Data collection is limited to the period between 2008, due to the international capital crisis and 2019, year of completion of the master's dissertation. Analysis was conducted with professionals who work directly with the issue of migration at the state level or in the city of Porto Alegre, professionals from 6 institutions were interviewed, accounting for 9 participants in all. The documentary analysis was performed considering international and national norms, as well as public policies developed in Brazil. The main results show the relationship between migration and the crisis of capital, and in times of crisis, migratory flows and the precariousness of labor that affects the working class as a whole, and particularly migrant workers, intensify. It was found that in Brazil the configuration of migrant work is articulated with the particularities of a peripheral and dependent country and with the history of selectivity and migratory restriction that articulated ethnic / racial discrimination, national security, subordination of migrant workers in relation to national ones. From the analysis of the empirical data it was realized that the “new faces of migration”, while being considered undesirable, experiencing expressions of racism through the advancement of neoconservativeism, also constitute themselves as desirable for capital that seeks to exacerbate the overexploitation of job.